Measurement and error of hoof horn growth rate in sheep - Shelton, J.; Usherwood, N.M.; Wapenaar, W.; Brennan, Marnie L.; Green, L.E. (Cambridge University Press, 2012)
Determining the rate of hoof horn growth in sheep is important for understanding the physiology and pathology of the foot and the impact of the environment and the treatment of diseased feet on foot health. It could lead to improved understanding of the interaction between hoof horn and pasture/barn floor characteristics and in methods for prevention and treatment of ovine foot diseases. In the current study, the hoof horn was measured using a previously tested protocol on all eight digits of 21 healthy yearling mule ewes on a farm in North Wales on four occasions over a period of 53 days. The mean hoof horn growth rate was 0·11 mm (s.e.m. 0·02) per day; the residual error variance was 0·024 and the R2 was 0·245. There were no significant differences between hoof horn growth rates in front and hind feet or between medial and lateral claws or over time.